Utilization of Vegetable Waste for Liquid Organic and Compost Fertilizer Production: A Training Program in Sukoreno Village - Agustina, Tata Amelia; Candra, Candra; Purnandani, Nabila Zahra; Sari, Nisa Fauziah Kurnia; Mas’audi, Ikhsan; Putra, Muhamad Rizky Juraeda; Salsabila, Arumsari Aryaning; Saraswati, Dina Ambar Ayu; Saputra, Farrel Rakha; Pradiva, Revalyna Ayu; Setiyaningrum, Daena; Puspita, Adelia Amel; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
The management of organic waste, particularly vegetable waste, remains a challenge in rural areas, as it is often underutilized and has the potential to cause environmental pollution. This outreach program aimed to enhance the knowledge and skills of the Women Farmers Group (KWT) in Sukoreno Village, Kaliwiro District, Wonosobo Regency, in processing vegetable waste into Liquid Organic Fertilizer (LOF) with both agronomic and economic benefits. The methods employed included material delivery, hands-on demonstrations of LOF production, and evaluation through question-and-answer sessions and participant practice observation. The results indicated an improvement in participants’ understanding of the importance of vegetable waste management, the materials required, and the stages of LOF production. Participants were able to explain the production procedures and perform them independently. This improved understanding is expected to reduce the accumulation of organic waste that may negatively impact the environment and public health, while also creating additional income opportunities for KWT members. Therefore, training on LOF production from vegetable waste proves effective as a community empowerment strategy for sustainable local resource management in rural areas.